Video Service Quality Guarantee over Smart TV Termial - Liang Yao; Qing Xiao; Weijia Shi; Xi Xi (Dianxin kexue)
With the development of internet business，intelligent terminals are becoming more and more popular.Faster CPU operating speed，more convenient operating system and flash and RAM with larger capacity than before are brought by terminal intelligence.Intelligent set-top box（STB）can support the IPTV service and OTT service at the same time.The method of estimating video quality experience，differences between IPTV and OTT service business realization mechanism in intelligent terminal was discussed.According to the difference between two types of video service，the method and requirement of quality assurance for video service was presented in the intelligent set-top box.